Applicability of Structural Health Monitoring of Bridges in Megaprojects - Gupta, Dinesh Kumar; Yadav, Raghabendra (KTFT Journal, 2024)
Nepal is currently experiencing significant growth in infrastructure development, with numerous bridge construction projects underway. Integrating health monitoring systems into these projects is crucial, aligning with global trends in infrastructure management. Implementing Structural Health Monitoring (SHM) systems using advanced sensors, data acquisition systems, and decision support mechanisms allows engineers to detect minute behavioral changes in critical infrastructure. This early detection capability enables timely interventions, enhancing structural safety and longevity. SHM systems can be tailored to meet specific operator and structure requirements, offering a cost-effective solution. With minimal installation costs, SHM can reduce overall maintenance and operational expenses by up to 98%, while providing invaluable life-saving warnings.